Development of a Tuition Center Information System - Chai, Kow Kim (2003)
The purpose of the project is to develop a tuition center information system which is data collecting and data processing system built with Visual Basic 6.0 programming language with Microsoft's Access as a database. The main objective of developing this system is to help administrator in managing the unavoidable administrative tasks such as student registration, and fee collecting. Benefit to public is that they can register on-line, check for timetable and tuition fee. And benefit for existing student, they are able to look for personal timetable and fee payment status.